Evaluation of anti-inflammatory compounds isolated from Millettia dielsiana Harms ex Diels by molecular docking method - Nguyen Xuan Ha; Vu Thi Thu Le; Do Tien Lam; Pham Minh Quan; Vu Thanh Dat (Vietnam Journal of Science and Technology, 2022)
In this study, we focused on screening and simulating the interaction between anti-inflammatory proteins and 50 compounds isolated from Millettia dielsiana Harms ex Diels. 39 out of 50 compounds that violated no of Lipinski’s rule of five were sorted out as favorable for drug development and selected for studies further. Then, a molecular docking study of compounds into the binding sites of COX-1 and COX-2 allowed shedding light on the binding mode of these potential COX inhibitors performed using Autodock Vina software. Our results showed that 6 compounds, including millesianin E (D32), barbigerone (D18), millesianin D (D31), (+)-epicatechin (D11), durallone (D17), and ichthynone (D19) exhibited good binding energy with the cyclooxygenase-2 (COX-2) enzyme meanwhile all of the selected compounds exhibited poor binding energy to the cyclooxygenase-1 (COX-1) enzyme. The binding energies of these compounds range from -8.6 kcal/mol to -9.0 kcal/mol better than the standard compounds Valdecoxib and Lumiracoxib. In addition, an analysis of the COX-2 enzyme and selected compounds binding was also presented. The important binding modes shown at the active site of the COX-2 enzyme through hydrogen bonds compared with standard compounds showed this as potential candidates against this enzyme. Therefore, these results might give a positive signal in finding anti-inflammatory drugs from Millettia dielsiana.